Do Senohrab jezdí kde kdo: Sociální a krajinotvorné aspekty vývoje přípražského letoviska v 19. a v první polovině 20. století - Chaloupková, Romana; Matoušek, Václav (Lidé města, 2020)
Beginning in 1850, colonies of recreational villas for the upper and upper-middle classes of Prague entrepreneurs and the intellectual elite began springing up in countryside outside of Prague in a radius of 30 kilometres. They were usually established in an agricultural landscape, in river and creek valleys, surrounded by forested hills. The condition was to have a direct rail commute from Prague. As a rule, the establishment of villa colonies was preceded by the stays of Prague denizens in summer flats run by the local farmers or in the local hotels and guesthouses. The actual establishment of the recreational colony was often a business venture of the locals or of Prague entrepreneurs. The recreational villa colony in Senohraby, located on the Emperor Franz Josef Railway near the confluence of Mnichovka Creek and Sázava River, was established as one of the last colonies around Prague by a group of four local as well as Prague developers and constructors in 1895. In 1918, a turn of events in the developments of elite villa colonies for the upper classes of Prague occurred when the Austro-Hungarian Empire fell, or when the independent Czechoslovak Republic was established, respectively. The forests in the proximity of the confluence of the Mnichovka and the Sázava were first overtaken by “tramps” (from the so-called tramping movement) hailing from the lower classes of Prague, and later by conformist recreation-seekers from the middle and lower classes. Despite of being conformist, many such recreation-seekers stylised their abodes-cabins to evoke the non-conformist manner typical for tramping holidays. During World War II, German occupants took over the resort in Senohraby.